Pharmaceutical Evaluation of Brihatpanchamoola Kwatha Prepared By Root Bark And Stem Bark - Vyas, Manish (International Journal of Pharmaceutical & Biological Archive, 2011)
Brihatpanchamoola is an extensively used Ayurvedic combination of five root barks for curing different diseases. However, as per requirements, the root bark of these drugs are not available in the market. Therefore, many industries are using stem bark instead of root bark during preparation of respective formulations. Thus, in the present study, the Kwatha prepared from root bark and stem bark of Brihatpanchamoola has been evaluated on analytical parameters. The organoleptic, physicochemical characteristics and qualitative estimation of functional groups for both the samples revealed similar results except for the absence of saponins in root samples. HPTLC profile showed presence of more chemical moieties in raw stem bark in comparison to root bark. However, these findings were reversed in case of Kwatha prepared from the same. Analytically, the study reveals that root bark of Brihatpanchamoola can be effectively substituted by stem bark for almost all practical purposes.